Synaesthetic emergence: a scoping review of factors facilitating synaesthetic states in non-synaesthetes through arts engagement - Dominik Havsteen-Franklin; Valeria Perboni (Cogent Arts & Humanities)
Synaesthesia is defined as a multi-sensory phenomenon in which one sense can be triggered by another without external stimuli, for example seeing colours when hearing music. This paper maps findings from the literature to describe what elements of arts engagement facilitate synaesthetic experiences among non-synaesthetes. The rationale for this study is on the basis that evidence shows multi-sensory experiences underpin creative innovations and serve as a foundation for embodied wellbeing practices. Through a scoping review guided by the PRISMA-ScR framework, this study identifies eight interdependent themes within which combinations of factors have the potential to produce synaesthetic states: Inviting Co-creation, Participatory Embodiment, Cultural and Social Engagement, Embodying Cognition, Producing Affective Intensity, Stimulating Associative Memory, Unifying Sensory Engagement, and Sensory Digital Enhancement. The review spans a diverse array of arts engagement practices, music, dance, visual arts, performance, and culinary events, to investigate how these modalities can evoke synaesthetic experiences in non-synaesthetes. The methodology employs deductive thematic synthesis informed by a new materialist perspective. The findings support the hypothesis that under particular conditions co-creative arts engagement can blur traditional sensorial boundaries, demonstrating that participatory arts can elicit embodied synaesthetic states in non-synaesthetes. The study also provides insights into how synaesthestic experiences in arts engagement influences perception, cognition, and social interaction, offering innovative pathways to enhance wellbeing and promote social cohesion. These findings have implications for the use of arts-based interventions in fostering multi-sensory engagement and expanding understanding of synaesthetic states with non-synaesthetes and the potential effects on wellbeing.